CONCEPTUAL APPARATUS AND FACTORS OF COMPETITIVE STABILITY IN TECHNICAL AND ECONOMIC SYSTEMS - Stepan P. Burlankov; Mikhail A. Ananiev; Petr S. Burlankov; Alexander E. Skvortsov (Вестник Российского экономического университета имени Г. В. Плеханова)
Competitive stability of technical and economic systems (TES) as an ability to retain competitive advantages during a long period of time is determined by an average level of quality and prices of the output. In this connection it is necessary to develop new approaches and methods of managing internal competitive stability of all TES structures' interaction based on the use of market relations' tools. The article provides a conceptual apparatus of the development of competitive stability of technical and economic systems by key stages of reproduction. The author puts forward his own definitions of competition, stability and competitive stability of TES and shows levels of competitive stability of technical and economic systems.